Is there a sub-parsec-scale jet base in the nearby dwarf galaxy NGC 4395?. Issue 4 (24th June 2022) - Yang, Jun; Yang, Xiaolong; Wrobel, Joan M; Paragi, Zsolt; Gurvits, Leonid I; Ho, Luis C; Nyland, Kristina; Fan, Lulu; Tafoya, Daniel
ABSTRACT: NGC 4395 is a dwarf galaxy at a distance of about 4.3 Mpc (scale: ∼0.021 pc mas −1 ). It hosts an intermediate-mass black hole (IMBH) with a mass between ∼10 4 and ∼10 5 solar masses. The early radio observations of NGC 4395 with the very long baseline interferometry (VLBI) network, High Sensitivity Array (HSA), at 1.4 GHz in 2005 showed that its nucleus has a sub-mJy outflow-like feature (E) extending over 15 mas. To probe the possibility of the feature E as a continuous jet with a base physically coupled with the accretion disc, we performed deep VLBI observations with the European VLBI Network (EVN) at 5 GHz, and analysed the archival data obtained with the HSA at 1.4 GHz in 2008, NSF's Karl G. Jansky Very Large Array (VLA) at 12–18 GHz and the Atacama Large Millimetre/submillimetre Array (ALMA) at 237 GHz. The feature E displays more diffuse structure in the HSA image of 2008 and has no compact substructure detected in the EVN image. Together with the optically thin steep spectrum and the extremely large angular offset (about 220 mas) from the accurate optical Gaia position, we explain the feature E as nuclear shocks likely formed by the IMBH's episodic ejection or wide-angle outflow. The VLA and ALMA observations find a sub-mJy pc-scale diffuse feature, possibly tracing a thermal free–free emission region near the IMBH. There is no detection of a jet base at the IMBH position in the VLBI maps. The non-detections give an extremely low luminosity of ≤4.7 × 10 33 erg s −1 at 5 GHz and indicate no evidence of a disc-jet coupling on sub-pc scales.